Work from Home Success: Agile work characteristics and the Mediating Effect of supportive HRM - Lukas Heidt; Felix Gauger; Andreas Pfnür (Review of Managerial Science, 2022)
Work from home or teleworking, continues to expand not least due to the COVID-19-crisis and poses challenges for employees and companies. In uncertain and dynamic times, organisations wonder what skills make employees successful when working from home and which measures support employees. By performing in-depth research that addresses employee agility as skills and capabilities, a research framework is proposed. Based on an international survey of employees working from home during the COVID-19-crisis (N0.167em=0.167em1,016), the impact of agile work characteristics on work from home success and the mediating effect (accounting for 48% of the total effect) of tailored support measures by HRM were investigated. The results of the mediation analysis show that agile work characteristics have a direct, positive and significant effect on the success of working from home. Part of the effect is explained by HRM measures as a mediator. The findings contribute to the research stream of dynamic capabilities by applying the theory to working from home. The comparatively simple research model provides companies with information on how they can best support employees in the dynamics of a crisis and the expansion of work from home and, therefore, has high relevance for practitioners.
Keywords: M10; M12; M14; M59; D22; D23; 650; Agile workforce; Telework; Work from Home; Dynamic capabilities; HRM; Firm success